Coronal brain atlas in stereotaxic coordinates of the African spiny mouse, acomys cahirinus - Vitorino, Marta (2022)
The African spiny mouse (Acomys cahirinus) is an emerging model of mammalian epimorphic regeneration that has aroused the interest of the scientific community in the last decade. To date, studies on brain repair have been hindered by the lack of knowledge on the neuroanatomy of this species. Here, we present a coronal brain atlas in stereotaxic coordinates, which allows for three-dimensional identification and localization of the brain structures of this species. The brain of 12-week-old spiny mice was mapped in stereotaxic coordinates using cresyl violet-stained brain sections obtained from coronal cryosectioning of the brain after transcardial perfusion with fixative. The atlas is presented in 42 plates representing sections spaced 240 mu m apart. Stereotaxic coordinates were validated using both a model of Parkinsonian lesion of the striatum with 6-hydroxydopamine and labeling of the corticospinal tract in the spiny mouse spinal cord using AAV1/2-GFP intracortical injections. This work presents a new tool in A. cahirinus neurobiology and opens new avenues of research for the investigation of the regenerative ability of A. cahirinus in models of brain disorders.